(untitled) (Research, Society and Development, 2022)
This study addresses the benefits of pharmaceutical care practice in patients with type 2 Diabetes Mellitus (DM), a disease that has a slow development and long duration, and which is due to the intensity of the degree of blood sugar elevation, which, if there is no treatment, may cause serious damage to the human body. Its general objective is:To analyze the benefits and importance of pharmaceutical care for patients with type 2 diabetes, emerging the need for the pharmacist in drug therapy and treatment of the disease. To carry out this work, the method of systematic review was used, with contextualized surveys in an electronic database. The keywords were used: Pharmaceutical Care, Diabetes and drug therapy. Inclusion Criteria: observational and analytical studies. Articles involving non-human models, randomized trials were excluded. 124 studies were identified, of which 63 were excluded and 61 selected for analysis. Initially, 23 studies of interest were chosen, where 06 were outside the focus of the study, 02 incomplete and 05 in other languages. 10 studies were used as the main ones and another 13 were used as argumentative support. Concludes DM is a socially significant disease that causes complications concomitant with other complications affecting the patient’s quality of life and work, which can lead to disability and premature death. Pharmaceutical Assistance aims to prevent the development of complications, detect and control DM and, above all, the rational use of medicines.